Тезисы докладов XXVI итоговой студенческой научной конференции (1998)
Экземпляры: КР (20020117) / Инвентарный номер: у53310 / Цена: 15.00 / Сис.шифр: 74.48 / Авт.знак: У 30 / ГРНТИ: 14 / ББК: 74.480.27